2016
DOI: 10.2134/jeq2014.12.0521
|View full text |Cite
|
Sign up to set email alerts
|

Urban Soil: Assessing Ground Cover Impact on Surface Temperature and Thermal Comfort

Abstract: The urban population growth, together with the contemporary deindustrialization of metropolitan areas, has resulted in a large amount of available land with new possible uses. It is well known that urban green areas provide several benefits in the surrounding environment, such as the improvement of thermal comfort conditions for the population during summer heat waves. The purpose of this study is to provide useful information on thermal regimes of urban soils to urban planners to be used during an urban trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Soil temperature sensors were buried horizontally 10 mm deep. This network operated continuously from 1 June 2014 to the end of August 2014 (Brandani et al, 2015). For each surface and exposition, T s at noon was measured by an infrared thermometer (IR) (Agri-Therm II, Everest Intersciences) as the mean of five measurements collected between 12:00 and 13:00.…”
Section: Study Sitementioning
confidence: 99%
“…Soil temperature sensors were buried horizontally 10 mm deep. This network operated continuously from 1 June 2014 to the end of August 2014 (Brandani et al, 2015). For each surface and exposition, T s at noon was measured by an infrared thermometer (IR) (Agri-Therm II, Everest Intersciences) as the mean of five measurements collected between 12:00 and 13:00.…”
Section: Study Sitementioning
confidence: 99%
“…One such benefit is improvement of the thermal comfort condition of city residents during peak summer months by mitigating the urban heat island effect. The study conducted by Brandani et al (2016) provides useful information on thermal regimes of urban soils and surfaces and demonstrates that exposed surfaces became less heated if their albedo was high, which led to significant reduction in surface temperatures even under the sun's direct exposure. The authors compared four different surfaces, showing that green surfaces were always cooler than asphalt, gray sandstone, and white gravel, as indicated by lower daytime surface and air temperatures.…”
Section: Benefits Of Urban Green Spacesmentioning
confidence: 99%
“…Hence, as well as being a measure of how uncomfortable a surface may be for pedestrians, surface temperature also affects the amount of heat available for storage in the LE. Many studies of urban LE surface temperatures have been undertaken [4,13,15,[21][22][23][24][25][26][27][28]. In general, these studies found that manufactured, low albedo and dry materials were hotter than plants or than LEs that were moist or had higher albedos.…”
Section: Introductionmentioning
confidence: 99%